The Influence of Free Cash Flow and Firm Size on Firm Value: Mediation of Debt Policy - Yana, Cindhi Hesti; Yuniati, R. A Norromadani; Dewi, Arfiana (Universitas Mercu Buana, 2024)
Firm value is defined as the investor's view of the company's level of success in managing company resources. This research was conducted to analyze the influence of free cash flow and company size on company value with debt policy as an intervening variable. The population in this study was transportation and logistics sector companies registered on the IDX using purposive sampling. The sample used in this research was 17 companies. The way to test the influence between variables is to test panel data regression analysis and path analysis. The research results show that free cash flow and company size do not affect company value. Free cash flow and company size do not affect debt policy. The intervening variable, debt policy, cannot mediate the influence of free cash flow and company size on debt policy. Companies in the transportation and logistics sector need to increase their free cash flow and optimize their asset numbers to attract investors' attention, which can influence investment decisions and indicate an increase in company value.